Robert A. Lovett and the Development of American Air Power - Jordan, David M., 1935- (McFarland & Company, Inc., Publishers, 2018)
"Robert Lovett grew up in Texas, went to Yale, and earned his wings as a naval air force hero in World War I. He played a key role in the development of the Army Air Force in World War II. His emphasis on strategic bombing was instrumental in defeating Hitler's Germany"--